The Development of Renewable Energy Sources in Turkey - ÇETİN, Atalay and VARDAR, Ali (European Journal of Sustainable Development, 2014)
Especially in last two decades, most of the developed and developing countries around the world have been supporting the researches that investigate more clean and sustainable energy sources. Renewable energy sources play more important role in today’s increasingly globalized energy market because of the environmental issues and the sources of fossil fuel are becoming scarce. According to that, as a virtue of the rapidly increase in energy demand, the supply of renewable energy sources are increasingly continue around the world. As a matter of fact, when it is compared to the 2011 rates, the consumption rate of hydro-electricity and other renewable energy sources has increased to 4.3% and % 15.2 respectively in 2012 in the world, is verifying that view. The aim of this study is to investigate the present potential and sufficiency of the main sources of renewable energy such as solar, wind, hydropower, geothermal and biomass at Turkey. In this regard, even Turkey has a remarkable potential especially in hydro, wind, solar and geothermal energies among Europe, renewable energy sources ratio in Turkey’s total energy consumption is not rising at desired level. Furthermore because Turkey hasn’t got a rich fossil fuel reserves, it needs to import fossil energy sources to meet its rapidly growing energy needs. In related to this, Turkey’s current deficit has been growing due to the increase in fossil fuel sources prices at international energy markets. On the other side Turkey’s Green House Gases (GHGs) emission has grown more than two times as a result of its rapidly using of fossil fuel sources due to its growing economy, industrialization and urbanization process since 1990. Within this context, as a foreign dependent country on fossil fuel energy sources (especially on crude oil and natural gas), Turkey should rapidly change its energy policy from fossil fuels to renewable energy sources which are domestic, clean and much more cheaper. Keywords: Renewable Energy Potential; Turkey; Wind; Solar; Geothermal; Biomass; Hydropower.